2010
DOI: 10.1016/j.jsat.2009.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of organizational formation, innovation adoption, and dissemination activities within the National Drug Abuse Treatment Clinical Trials Network

Abstract: The National Institute on Drug Abuse (NIDA) established the National Drug Abuse Treatment Clinical Trials Network (CTN) to conduct trials of promising substance abuse treatment interventions in diverse clinical settings and to disseminate results of these trials. This paper focuses on three dimensions of the CTN’s organizational functioning. First, a longitudinal dataset is used to examine the CTN’s formation as a network of inter-organizational interaction among treatment practitioners and researchers. Data i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 22 publications
2
67
0
Order By: Relevance
“…Counselors' beliefs about ease of use, fit with ongoing practices, fit with personal values, and perceptions that a new practice will be "rewarded, supported, and expected" (Klein & Sorra, 1996, p. 1060 have been associated with the use of new practices (Frambach & Schillewaert, 2002;Knudsen & Studts, 2010;Rogers, 2003), as has practitioners' confidence in the evidence supporting a treatment approach (Roman et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Counselors' beliefs about ease of use, fit with ongoing practices, fit with personal values, and perceptions that a new practice will be "rewarded, supported, and expected" (Klein & Sorra, 1996, p. 1060 have been associated with the use of new practices (Frambach & Schillewaert, 2002;Knudsen & Studts, 2010;Rogers, 2003), as has practitioners' confidence in the evidence supporting a treatment approach (Roman et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research and theory are still better able to explain the "adoption" of an evidence-supported practice (i.e., an organizational decision to use a practice) than to explain "implementation" (i.e., practitioners' actual use of practices with clients; Fixsen et al, 2005;Rogers, 2003;Roman, Abraham, Rothrauff, & Knudsen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the first agencies that decided to adopt (early adopters) evidence-based mental health practices judged risks related to adoption to be smaller than agencies that did not decide to adopt the new practices and that the early adopters viewed the risks as more manageable. Roman, Knudsen, and colleagues (e.g., Knudsen, Ducharme, & Roman, 2007;Knudsen, Roman, & Oser, 2010;Roman, Abraham, Rothrauff, & Knudsen, 2010) have examined organizational and other factors affecting the adoption of medication-assisted treatment for substance abuse. Fully specified models of adoption or the adoption decision has not yet been developed.…”
Section: Adoption-the Process Of Deciding Whether To Use An Innovatiomentioning
confidence: 99%
“…Challenges still remain and are being studied in the US. [14][15][16][17][18] It is important to understand the challenges for adoption of EBPs in substance abuse treatment in Mexico as the network evolves.…”
Section: Introductionmentioning
confidence: 99%